Interplay Between Mitochondrial Oxidative Disorders and Proteostasis in Alzheimer’s Disease - Llanos-González, Emilio; Henares-Chavarino, Ángel Andres; Pedrero-Prieto, Cristina María; García-Carpintero, Sonia; Frontiñán-Rubio, Javier; Sancho-Bielsa, Francisco Javier; Alcain, Francisco Javier; Peinado, Juan Ramón; Rabanal-Ruíz, Yoana; Durán-Prado, Mario (Frontiers in Neuroscience, 2020)
Although the basis of Alzheimer’s disease (AD) etiology remains unknown, oxidative stress (OS) has been recognized as a prodromal factor associated to its progression. OS refers to an imbalance between oxidant and antioxidant systems, which usually consist in an overproduction of reactive oxygen species (ROS) and reactive nitrogen species (RNS) which overwhelms the intrinsic antioxidant defenses. Due to this increased production of ROS and RNS, several biological functions such as glucose metabolism or synaptic activity are impaired. In AD, growing evidence links the ROS-mediated damages with molecular targets including mitochondrial dynamics and function, protein quality control system, and autophagic pathways, affecting the proteostasis balance. In this scenario, OS should be considered as not only a major feature in the pathophysiology of AD but also a potential target to combat the progression of the disease. In this review, we will discuss the role of OS in mitochondrial dysfunction, protein quality control systems, and autophagy associated to AD and suggest innovative therapeutic strategies based on a better understanding of the role of OS and proteostasis.